2001
DOI: 10.2166/wst.2001.0535
|View full text |Cite
|
Sign up to set email alerts
|

Development of an odorant emission model for sewage treatment works

Abstract: In the field of odour assessment, much attention has been paid to the measurement of odour concentration. Whilst the concentration of an odour at a receptor is a useful indicator of annoyance, the concentration at the source tells only half the story. The emission rate - the product of odour concentration and air flow rate - is required to appreciate the significance of odour sources. Knowledge of emission rates allows odour sources to be ranked in terms of significance and facilitates appropriate selection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The detection and perception of odours by humans is an extremely complex process. The main factors determining whether an odour causes annoyance are the concentration of the odorous compound in the air, the "odour quality", the odour appearance frequency and the odour duration (Piringer et al 2007;Nicell 2003Nicell , 2009Gostelow et al 2001Gostelow et al , 2004Gallego et al 2008).…”
mentioning
confidence: 99%
“…The detection and perception of odours by humans is an extremely complex process. The main factors determining whether an odour causes annoyance are the concentration of the odorous compound in the air, the "odour quality", the odour appearance frequency and the odour duration (Piringer et al 2007;Nicell 2003Nicell , 2009Gostelow et al 2001Gostelow et al , 2004Gallego et al 2008).…”
mentioning
confidence: 99%
“…By knowing the values of the mass transfer coefficients in the interior of the flux hood, it is possible to estimate the bias in the measured emission rate, compared to the values that could be expected in the field in the absence of the sampling device, especially for compounds with volatilisation controlled by conditions in the gas phase. In the present analysis, the calculated by the volatilisation model proposed by Gostelow et al (2001a) for passive liquid surfaces is adopted as a proxy for the values in the field. The friction velocity, which is one of the input variables for the model, is estimated based on the wind speed at 10 m height ( ) by applying the correlation of Smith (1980).…”
Section: Relating Measurements Obtained With the Flux Hood And Field mentioning
confidence: 99%
“…Prediction of H 2 S emissions throughout WRRF units has been carried out by resorting to different models, such as WATER9 (USEPA, 2001), BASTE (Corsi and Card, 1991), TOXCHEMþ (Melcer et al, 1994) or the model proposed by Gostelow et al (2001b), among the most commonly used. Main H 2 S removal mechanisms considered include volatilization, stripping, adsorption, absorption, biodegradation (USE-PA, 2001) and oxidation (Santos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches exist for empirical derivations of these coefficients, as described by USEPA (1994), Mackay and Matsugu (1973) and Mackay and Yeun (1983). However, several authors have demonstrated the expressions often over or underestimate emission rates (Ferro and Pincince, 1996;Jones et al, 1996;Gostelow et al, 2001b;Santos et al, 2006) by factors of up to 12 times , depending on the operational process, and therefore local determination of transfer coefficients is advised. When modelling emissions within enclosed environments, some models, such as WATER9 (USEPA, 2001), are based on the assumption of the equilibrium of volatile compound concentration between the gas and liquid phase, rather than mass transfer phenomena (Tata et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation